Microbial community structure in major habitats above 6000 m on Mount Everest - Liu, Y. Q.; Yao, T. D.; Kang, S. C.; Jiao, N. Z.; Zeng, Y. H.; Huang, S. J.; Luo, T. W.; 焦念志 (2007)
Bacterial abundance in surface snow between 6600 and 8000 m a.s.l. on the northern slope of Mt. Everest was investigated by flow cytometry. Bacterial diversity in serac ice at 6000 m a.s.l., glacier meltwater at 6350 m, and surface snow at 6600 m a.s.l. was examined by constructing a 16S rRNA gene clone library. Bacterial abundance in snow was higher than that in the Antarctic but similar to other mountain regions in the world. Bacterial abundance in surface snow increased with altitude but showed no correlation with chemical parameters. Bacteria in the cryosphere on Mt. Everest were closely related to those isolated from soil, aquatic environments, plants, animals, humans and,other frozen environments. Bacterial community structures in major habitats above 6000 m were variable. The Cytophaga-Flavobacterium-Bacteroides (CFB) group absolutely dominated in glacial meltwater, while beta-Proteobacteria and the CFB group dominated in serac ice, and beta-Proteobacteria and Actinobacteria dominated in surface snow. The remarkable differences among the habitats were most likely due to the bacterial post-deposition changes during acclimation processes.